A new approach to measuring the liveability of cities: the Global Liveable Cities Index. (5th November 2014) - Giap, Tan Khee; Thye, Woo Wing; Aw, Grace
This paper advocates a new measure of liveability – the Global Liveable Cities Index (GLCI) – to rank the world's major cities. The GLCI advances the measurement of the 'liveability' construct by taking into account the multidimensional sensibility of diverse groups of ordinary persons across 64 cities. The paper also compares the GLCI with six well known city indices from the literature and finds that the GLCI performs as a relevant liveability indicator for diverse groups of ordinary persons. In addition, the paper conducts policy simulations to find that city planners interested in attracting talent of a given personality type can invest in areas with low scores in the GLCI.